The impact of tariff diversity on broadband diffusion: An empirical analysis - Justus Haucap; Ulrich Heimeshoff; Mirjam R. J. Lange (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2014)
This paper provides an empirical analysis how tariff diversity affects fixed-line broadband uptake, utilizing a new data set with 1497 fixed-line and 2158 mobile broadband tariffs from 91 countries across the globe. An instrumental variable approach is applied to estimate demand, controlling for various industry and socio-economic factors. The empirical results indicate that, firstly, lower prices, more tariff diversity and higher income increase broadband penetration. Secondly, inter-platform competition and mobile broadband prices are not found to have a significant effect on fixed-line broadband penetration. This suggests that low prices and the diversity of broadband offerings are more important drivers of fixed broadband adoption than competition between various technologies (cable networks, fixed-line telephone networks, mobile networks).
Keywords: L86; L96; 330; Broadband prices; Tariff diversity; Broadband demand; Broadband penetration; Broadband uptake; Price discrimination; Inter-platform competition